Reintroduction of vascular epiphytes in forest restoration plantations - Domene, Frederico (2018)
Epiphytic species are a key component of the structure and dynamics of tropical forests. Although frequently found in mature forests, these species have difficulty reestablishing in young forests (forest restoration plantings and secondary forests). Recent assessments of young forests shows that there has been success in carbon recovery, mainly because of the success in survival and development of tree species, which produce a forest structure similar to that found in mature forests. However, the species richness is much lower than the original one, especially when comparing the epiphyte species. The objective of this thesis was to answer questions essential to the enrichment of young forests, through the artificial transplantation of epiphytic species, mainly the effect of planting age, the place of transplant, the size of the seedlings and the host species used in the survival and development of the species transplant epiphytes. Eight epiphytic species (Araceae, Bromeliads, Cacti and Orchids) were studied. We evaluated potendial seed storage, seed germination, abiotic factors (Water, Light and Nutrients) that affect seedling production and transplant methods for young forests using seedlings and direct seeding. All epices are orthodox maintaining germination potential higher than 80% after 16 months of storage. Two species of cactus are positive photobatic, germinating only in the presence of light. The growth of the seedlings in greenhouse is strongly influenced by the nutrient supply. Both the fixation site and the size of seedlings do not interfere in the survival and development of the transplanted epiphyte species. The age of the forest is also not an important factor in the success of the transplanted epiphytes, being possible to use young forests (12-15 years). Direct sowing may be a promising method to enrich young plantations, but adjustments need to be made to provide higher survival rates for the seedlings. The transplantation of epiphytic species into young forests is a viable strategy to overcome the natural limitations of recolonization that these forests present. Future research and monitoring of transplanted epiphytes may determine the generality of our observations.